Revenge of the Chili Queens - Logan, Kylie (Logan, Kylie. Chili cook-off mysteries., 2015)
Everyone in San Antonio remembers the Alamo, but how many remember the Chili Queens? Back in the early twentieth century, these spicy señoras sold their lip-smacking chili in plazas all around the city. Now, as part of the Chili Showdown, Maxie and her half-sister, Sylvia, are dressing up as the Chili Queens to raise money for charity. But someone wasn't feeling too charitable toward a local troubadour, who is murdered at the fundraiser. When their friend Nick Falcone, head of security for the Showdown, actually becomes the prime suspect, it's up to Maxie and Sylvia to turn the heat up on a killer, who's planning a chili reception for them.